The Scottish experience in community energy development: A starting point for Chile. (October 2019) - Fuentes González, Fabián; Sauma, Enzo; van der Weijde, AdriaanHendrik
Abstract: This study presents an overview of the relevant evidence available up to now regarding the Scottish experience in relation to the development of community energy projects. Scotland has a relevant number of community energy projects which are generating energy, improving the quality of life of communities through sustainable initiatives. This is the result of the implementation of successful policies to encourage community energy by the Scottish government (in comparison with other countries). On the contrary, the Chilean community energy sector is still incipient, despite some interest; public policies have been focused on fostering the concept of distributed generation. Chilean community energy developments have not been analysed in any detail; this paper is a first attempt to do so, and to derive lessons from the Scottish experience that can be useful to Chilean policy makers. We summarise and analyse the Scottish and Chilean community energy sectors and their developments. We further analyse the current Chilean net billing scheme using concepts from game theory, showing that it may not be the best support mechanism for citizen-led energy production developments. Based on these analyses, we define a list of policy recommendations for Chile, which can help further development in the community energy sector. Highlights: Scotland should be recognised as a worldwide example in community energy. Community-oriented organisations seem to be leading community energy in Scotland. Chilean energy policies have focused on distributed generation schemes instead. Chilean net billing scheme is not always convenient for residential consumers. Community energy development might be a promising option for Chile.